Neural Correlates of Conscious Motion Perception - Boncompte, Gonzalo; Cosmelli, Diego (Frontiers in Human Neuroscience, 2018)
The nature of the proper neural signature of conscious perception remains a topic of active debate. Theoretical support from integrative theories of consciousness is consistent with such signature being P3b, one of the main candidates in the literature. Recent work has also put forward a mid-latency and more localized component, the Visual Awareness Negativity (VAN), as a proper Neural Correlate of Consciousness (NCC). Early local components like P1 have also been proposed. However, experiments exploring visual NCCs are conducted almost exclusively using static images as the content to be consciously perceived, favoring ventral stream processing, therefore limiting the scope of the NCCs that have been identified. Here we explored the visual NCCs isolating local motion, a dorsally processed feature, as the primary feature being consciously perceived. Physical equality between Seen and Unseen conditions in addition to a minimal contrast difference between target and no-target displays was employed. In agreement with previous literature, we found a P3b with a wide centro-parietal distribution that strongly correlated with the detection of the stimuli. P3b magnitude was larger for Seen vs Unseen conditions, a result that was consistently observed at the single subject level. In contrast, we were unable to detect VAN in our data, regardless of whether the subject perceived or not the stimuli. In the 200-300 ms time window we found a N2pc component, consistent with the high attentional demands of our task. Early components like P1 were not observed in our data, in agreement with their proposed role in the processing of visual features, but not as proper NCCs. Our results extend the role of P3b as a content independent NCC to conscious visual motion perception.